An Analysis Of Culture Shock Faced By Main Character In Bajrangi Bhaijaan Movie - Yohana Restu Wilistia; Lina Tri Astuty Beru Sembiring; Ami Pradana (Multidisciplinary Journals, 2026)
Culture shock refers to a psychological and emotional response experienced by individuals when they are exposed to a culture that differs significantly from their own. the objectives of this research are to analyze phases and the effects of culture shock which are experienced by the characters in Bajrangi Baijhaan. This study used a descriptive qualitative method. The data of this research was taken from the movie Bajrangi Bhaijaan. This movie is also the object of this research. the researcher used only two types of instruments, checklists and observation documentation obtained from the research object. There were two kinds of observation used by the researcher, namely; the phases of culture shock and the effect of culture shock checklist. Both of the checklist was adapted from the theory by Ward (2001).  The findings revealed that there are four phases of culture shock experienced by the characters in the Bajrangi Baijhaan movie, namely; honeymoon, crisis, recovery, and adaptation phase. The Crisis phase appears most frequently, with 5 scenes, followed by the Adaptation phase with 3 scenes, the Recovery phase with 1 scene,  and finally the Honeymoon phase with 1 scene. Furthermore, the effects of culture shock in Bajrangi Bhaijaan movie are balanced between negative and positive. The experience of culture shock in the Bajrangi Bhaijaan movie begins with various negative effects such as fear, anxiety, and confusion arising from differences in language, religion, and nationality. However, as the story develops, many positive effects also emerge, including empathy, courage, gratitude, and peace.